2010
DOI: 10.1007/s00345-010-0538-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with survivin as a biomarker for urothelial bladder cancer

Abstract: In present group of patients, survivin was a reliable biomarker for high-grade urothelial BC (sensitivity 83%), but not for low grade (sensitivity 35%) urothelial BC with a high specificity (88%). No confounders influencing the results of survivin measurements could be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 17 publications
0
26
1
Order By: Relevance
“…Previously published studies showed specificities between 88% and 100% and sensitivities between 53% and 100% [28][30], [32][34]. While our results showed a similar specificity (98%) the sensitivity (21%) was markedly lower in this cohort study.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Previously published studies showed specificities between 88% and 100% and sensitivities between 53% and 100% [28][30], [32][34]. While our results showed a similar specificity (98%) the sensitivity (21%) was markedly lower in this cohort study.…”
Section: Discussioncontrasting
confidence: 56%
“…Due to the fact that non-invasive detection in urine samples is possible, survivin could be used specifically for screening of urogenital malignancies. Several studies, mostly of cross-sectional design and with a relatively limited number of cases, have demonstrated that survivin is a promising candidate for further validation in longitudinal studies [28][34]. Shariat et al performed a larger prospective study on recurrent bladder cancer that was based on immunohistochemical staining of tumor samples.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for study exclusion were as follows: other languages (six); review of literature (five) or editorial (one); report of previously reported data (one); required study design not met (five); other procedures (two); and other endpoint (two). Finally, 14 studies were included [14–27]. Two studies had two subsets of data [14,27].…”
Section: Resultsmentioning
confidence: 99%
“…A protein survivin, which was upregulated in high-grade BC, could be shown to be downregulated in miR-1826 transfected BC cell lines. [2173] In the same study, three oncogenes, i.e., beta-catenin, mitogen-activated protein kinase 1, and vascular endothelial growth factor C were shown as targets of miR-1826, which was confirmed through Western blotting technique. [21] Limitations to miRNA-based cancer therapy such as unstable nature of miRNA, their rapid plasma clearance and poor uptake into the tumor cells are challenging.…”
Section: Bladder Cancer Biology and Micro Rnamentioning
confidence: 87%